Social Media Marketing and Brand Loyalty: Analyzing the Mediating Role of Brand Trust - Srivastava , Praveen; Gupta , S.L.; Mishra, Niraj; Srivastava , Shelly; Mangla, Sanjay Kumar (Thailand and The World Economy, 2022)
In today's connected world, social media is a sound business strategy that is embedded in an online network. It allows businesses to create customer engagement by helping them develop their brand, enhance their networking capacity, and increase their customer base. Marketers should take advantage of B2C social media's potential to promote high brand awareness by faster realization of the importance of it as a business-to-consumer (B2C) strategy. Though the impact of social media is increasing, marketers appear to have ignored the full influence of social media. Although companies have taken to social media to improve their consumer and brand loyalty, the issue persists as to how to successfully create brand loyalty on social media. The study has investigated the mediating role of Brand Trust (BT) in the relationship between Social Media Marketing (SMM) and Brand Loyalty (BL). Since the SMM is perceived to be the new world concept being adopted mostly by the new generation (young) customers, the study has also investigated whether age moderates the influence of SMM on BL or whether it is indifferent to the age of the users. Data has been collected on social media users and SmartPls has been used to test the model to find out the association between different variables of the study.